UPLC-MS/MS and HS-SPME-GC–MS reveal the flavor profiles of two geographical indications woody vegetables: Staphylea bumalda and Staphylea holocarpa - Tao Zheng; Zhuang Deng; Min Tian; Qi Tang; Zhubing Hu; Guodong Wang; Haitao Zeng (Food Chemistry: X)
Staphylea bumalda (SHC) and Staphylea holocarpa (PGG) were recognized as geographical indication agricultural products due to unique flavor. 1218 differential non-volatile compounds and 536 differential volatile compounds were detected and identified through UPLC-MS/MS and HS-SPME-GC–MS methods. In SHC samples, catechins, epicatechins, proanthocyanidins, quinic acid derivatives, and kaempferol glycoside derivatives were the main flavor compounds, with bitter and harsh taste. L-tartaric acid, citraconic acid and citric acid were contributed to increase acidity. 4-Hexen-1-ol acetate, butanoic acid butyl ester, 3-Hexen-1-ol acetate, (E)-, and 3-Hexen-1-ol acetate, (Z)- were identified as characteristic odor compounds with strong floral, fruity and sweet odor. In PGG samples, epicatechin gallate, quercetin glycoside derivatives, L-histidine, and L-tyrosine were the leading contributors to bitter and harsh taste. The spicy, herbal, and bad smell odor were mainly brought by 2-octanol, and 3-Octen-1-ol, (Z)-. Our results offered comprehensive insights into the flavor and quality characteristics differences between PGG and SHC.